Managing Green Space to Achieve Sustainability of Infrastructure at IPB University - Heriansyah Putra; Febrian R Hidayat; Sutoyo Sutoyo; Ibnul Qayim; Anisa D Utami; Alim S Slamet (Universitas Diponegoro, 2024)
IPB University, Indonesia, has 18 campuses and is designed as a sustainable university. With a total area of 1669 Ha, IPB University has been beneficial in managing the massive area of campus site infrastructure. Managing the infrastructure development that considers the open space, including the forests, planted vegetation, and the ground surface for water absorption, is essential to achieve the sustainability of the infrastructure at IPB University. This paper presents the lessons learned from IPB University's campus setting in managing infrastructure development, focusing on developing open space, forests, and planted vegetation. Managing infrastructure development on campus to support the increasing number of students and the development of education, research, and campus activities faces various challenges. For this, IPB University provides a master plan as a policy and control system to ensure that all developed infrastructure has the goal of supporting campus activities and is highly considered for the sustainability of open spaces on campus.